2020
DOI: 10.5539/sar.v9n3p87
|View full text |Cite
|
Sign up to set email alerts
|

Concentration, Temperature and Storage duration Influence Chemical Stability of Compost Tea

Abstract: Chemical stability is one of the key quality control criterion for complex degradable materials with an active microbial community like compost tea, but largely understudied. A laboratory study was performed to assess the chemical stability of varying concentrations (0, 2.5, 5, 10, 15, 20, 30, 50 and 100%) of municipal solid waste (MSW) compost tea stored at different temperatures (4°, 10°, 22° and 35°C) and storage time (0, 13, 26 39 and 52 days). A 2-dimension principal compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…0.3-0.4% per dry weight) [33]. Hence, the low salt content of the pine wood PA. A recent study revealed that the salinity of a solution exhibits a strong association with its total dissolve solids (TDS) and electrical conductivity (EC) [34]. TDS content represents the amount of inorganic salt and little organic substances dissolved in a solution.…”
Section: Chemical Qualities and Antioxidant Activitiesmentioning
confidence: 99%
“…0.3-0.4% per dry weight) [33]. Hence, the low salt content of the pine wood PA. A recent study revealed that the salinity of a solution exhibits a strong association with its total dissolve solids (TDS) and electrical conductivity (EC) [34]. TDS content represents the amount of inorganic salt and little organic substances dissolved in a solution.…”
Section: Chemical Qualities and Antioxidant Activitiesmentioning
confidence: 99%